2021
DOI: 10.1080/02699206.2021.1874055
|View full text |Cite
|
Sign up to set email alerts
|

Students’ views and experiences of the training and use of phonetic transcription in speech and language therapy – the Irish perspective

Abstract: Phonetic transcription is an essential skill for a practicing speech and language therapist (SLT) required during the assessment, diagnosis and management of clients with speech difficulties. It is vital that appropriate training is received by student SLTs to ensure that they carry out phonetic transcription accurately and reliably once out in the workplace. This study investigates the views and experiences of final year SLT students regarding the training in phonetic transcription they received in university… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Narrow transcription is recommended for cleft palate or hearing‐impaired speech in clinical guidance (CSDRN, 2017), and was reportedly used by specialist SLTs working with those populations in Knight et al.’s (2018) survey. Studies involving SLT students have similarly found that their experience of seeing or using narrow transcription is almost exclusively restricted to cleft palate and hearing impairment contexts (e.g., Shaw & Yanushevskaya, 2021; Windsor, 2011). When recommending narrow transcription for these populations, however, the CSDRN guidelines do not specify whether all segments should be transcribed narrowly (including, for example, acceptable allophonic realizations) or only the disordered realizations, and in Knight et al.…”
Section: Introductionmentioning
confidence: 99%
“…Narrow transcription is recommended for cleft palate or hearing‐impaired speech in clinical guidance (CSDRN, 2017), and was reportedly used by specialist SLTs working with those populations in Knight et al.’s (2018) survey. Studies involving SLT students have similarly found that their experience of seeing or using narrow transcription is almost exclusively restricted to cleft palate and hearing impairment contexts (e.g., Shaw & Yanushevskaya, 2021; Windsor, 2011). When recommending narrow transcription for these populations, however, the CSDRN guidelines do not specify whether all segments should be transcribed narrowly (including, for example, acceptable allophonic realizations) or only the disordered realizations, and in Knight et al.…”
Section: Introductionmentioning
confidence: 99%